2005
DOI: 10.1029/2004gl022008
|View full text |Cite
|
Sign up to set email alerts
|

Medium energy pitch angle distribution during substorm injected electron clouds

Abstract: [1] An investigation of pitch angle resolved electron data of energy <47 keV made by the MPA instrument on LANL geosynchronous satellites reveals a signature of symmetric peaks in the pitch angle distributions, observed to expand from being nearly at perpendicular pitch angles ($90°) to nearly field aligned at lower energies. This feature is seen in almost every interval of increased fluxes at geosynchronous orbit. A closer examination reveals the expansion of the peak in pitch angle to be such that the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…This assumption is consistent with past work which has indicated that suprathermal fluxes are generally isotropic , and even if some anisotropy is present, it does not affect the Landau damping rates appreciably [Thorne and Horne, 1994]. The assumption of suprathermal flux isotropy is particularly valid during active times (which are of most interest to us in the present study) when the presence of intense waves tends to isotropise the electron distribution [Asnes et al, 2005] at lower energies.…”
Section: Ray Tracing Methodologysupporting
confidence: 79%
“…This assumption is consistent with past work which has indicated that suprathermal fluxes are generally isotropic , and even if some anisotropy is present, it does not affect the Landau damping rates appreciably [Thorne and Horne, 1994]. The assumption of suprathermal flux isotropy is particularly valid during active times (which are of most interest to us in the present study) when the presence of intense waves tends to isotropise the electron distribution [Asnes et al, 2005] at lower energies.…”
Section: Ray Tracing Methodologysupporting
confidence: 79%
“… Meredith et al [1999] have reported the observations of characteristic distributions in the restricted region at the equator outside the plasmapause, where the pitch angle distributions are formed with sharply peaked at 90° in the relatively low energy range below a few keV, which is known as a pancake distribution [ Wrenn et al , 1979]. Similar types of pitch angle distributions in keV combined with butterfly distributions were reported [ Åsnes et al , 2005]. It has been suggested that ECH (Electron Cyclotron Harmonic) waves are responsible for the formation of pancake distributions [ Meredith et al , 2000].…”
Section: Introductionmentioning
confidence: 81%
“…Other particle distributions with a considerably greater spread along the longitudinal velocity were also obtained in the RB (Bell et al, 2000;Asnes et al, 2005). Actually, whistler waves exist in a certain frequency band, which is determined by the mean distribution function anisotropy, frequency dependence of the magnetospheric resonator quality, and special features of the wave ray tracing.…”
Section: Introductionmentioning
confidence: 88%
“…1) near the magnetic equator plane in the RB has recently been obtained in the space experiments. Asnes et al (2005) give experimental data obtained using the Magnetospheric Plasma Analyser (MPA) instrument onboard the LANL geosynchronous satellites, according to which pancake-like distributions of the energetic electrons with energies less than 47 keV can exist. The authors consider such distributions as resulting from the wave-particle interaction with chorus emissions outside the plasmasphere due to the Cherenkov resonance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation